INTRODUCTION OF PATIENTS WITH CYSTIC OCCURRENCES IN ADOLESCENT AGE. - Kodirova Ziyodakhon Avazbek qizi,; Akramova Nozima Akramovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Testicular cystic formations in adolescents are a rare but clinically significant pathology that requires an individual approach to diagnosis and treatment. This paper analyzes modern scientific data and clinical observations regarding the management of adolescents with this pathology. The main attention is paid to the use of ultrasound as the main method of diagnosis and the determination of criteria for choosing between conservative treatment and surgical intervention. The results of the study confirm that dynamic observation is effective in most cases, while surgical treatment is required only with pronounced symptoms or a high risk of complications. The work highlights the need for further study of this issue in order to develop unified patient management protocols.